تاثير استراتجيتي التعلم النشط والمنظم ذاتيا في تعلم مهارتي حائط الصد والتصويب بكرة اليد لدى طالبات الصف الرابع الاعدادي - نهى عناية حاجم (الرياضة المعاصرة, 2015)
The study aimed to identify the effect of active learning strategy and learning self-organized learning my skills bulwark and correction hand reel with students fourth preparatory grade, and any of the two strategies (active and orderly learning self) more influential in the learning, the researcher used the experimental method to design two experimental groups equal with setting arbitrator Balachtbarren pre and post, on a sample of students in junior high valor for girls of their number (40) students were divided into two experimental introduced the first experimental group (active learning strategy) experimental and the second group (organized learning strategy self) to learn the skills are under allocated for each skill (4) the educational modules for a period of (8) weeks by educational unit one week targeted researcher section including the president of his time (35 minutes), and after processing the results were the main conclusions that each of the two strategies skill learning the skills of the correction and bulwark hand reel with students fourth grade improvement Intermediate, and learning strategy organized learning is most effective in improving the learning